THE REPRESENTATION OF TURN-TAKING STRATEGIES IN THE 2022 ELECTION DEBATE OF AUSTRALIAN PRIME MINISTER - Angga, Monika; Sunra, La; Hasbi, Muh (Journal of English Literature and Linguistic Studies, 2023)
This research discusses the representation of turn-taking strategies in the 2022 election debate of Australian Prime Minister. Therefore, the purposes of this research are to identify the types of turn-taking strategies, to find out the dominant type of turn-taking strategies, and to investigate the non-verbal signals of turn-taking strategies in the 2022 election debate of Australian Prime Minister. In doing this research, the writers used a descriptive qualitative method to analyze the selected data which are taken from three YouTube channels of Australia, and the data were classified based on the theory of turn-taking by Stenstrom (1994) and the theory of non-verbal signals by Yang (2011). As a result, the writers found 299 utterances containing turn-taking. The writers found that the debaters used all kinds of turn-taking strategy in their utterances. But, the most dominant turn-taking strategy used is holding the turn (178 utterances), followed by taking the turn (108 utterances), and yielding the turn (13 utterances). The debate is dominated by holding the turn strategy because the debaters were always trying to hold their turn to express their points of view. In order to hold the turn to speak, the debaters mostly used verbal fillers (124 utterances)—can be seen in appendix A—which gives the biggest contribution to the percentage. The rest are not give as big contribution as verbal fillers. And there are 5 situations where the debaters are noticed using non-verbal signals such as body movement, hand gestures, head movement, and facial expression, in order to take, to hold, and to yield their turn.